SMALL SCALE ORGANIC PADDY FARMING IN WEST SUMATRA: POTENCIES, CHALLENGES AND STRATEGIES - Idris, Idris; Amar, Syamsul; Sofyan, Efrizal; Adry, Melti Roza; Putri, Dewi Zaini; Sari, Yollit Permata; Yeni, Isra (Jurnal AGRISEP, 2022)
This study aims to analyse the potencies, challenges and strategy to develop organic paddy farming in West Sumatra. The selection of study area used a snowball sampling technique. To get the characteristics, potencies and challenges faced by farmers in the development of organic paddy, the researchers conducted a survey by using simple random sampling. In total, 144 organic farmers were chosen from cities and districts. Based on the results obtained from the survey, the researchers conducted in-depth interviews related to the potencies, challenges and strategies of developing organic paddy in West Sumatra. Those strategies were analyzed using SWOT analysis. The results show that organic paddy farming in West Sumatra has the potential to develop despite of the existing of challenges. The potencies of organic farming are discussed in several aspects such as government support, economic, environmental and health benefit. Nevertheless, the main serious problem that often encountered are land ownership, marketing, and quality as well as quantity issues. Moreover, the strategy that can be taken into account is to strengthen the government support and market networth and establish integrated pest control field schools.